PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR CAMAT MEDAN PETISAH - Kerisnasari Gulo, Elfina; Giawa, Yutina; Tarigan, Jenni (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2023)
In general, the goal of every company, both private and public, is to improve the quality of its human resources to produce good performance. This research was conducted to determine the influence of Leadership, Motivation and Work Environment on the Performance of Civil Servants at the Medan Petisah Sub-district Office. The sample used amounted to 32 respondents. This study used a quantitative method with data collection techniques through distributing questionnaires. The data analysis technique used was multiple linear regression analysis using the SPSS Version 22 program. The results showed that the regression equation Y=12.801+0.426X1+0.607X2+0.030X3. The results of this research show that leadership partially has a significant effect on employee performance with a t-count > t-table (3.027 > 2.048) and a sig value (0.005 <0.05). Motivation partially has a significant effect on employee performance with t-count > t-table (5.891 > 2.048) and sig value (0.000 <0.05). The work environment partially has no significant effect on employee performance with a t-count < t-table (0.214 < 2.048) and a sig value (0.832 > 0.05). Leadership, Motivation and Work Environment simultaneously have a positive and significant effect on Employee Performance with Fcount > Ftable (116.027 > 2.95) with a sig value (0.000 <0.05). The coefficient of determination of Adjuted R Square is 0.918 which means 91.8% of employee performance at the Medan Petisah Sub-District Office is influenced by the variables of Leadership, Motivation and Work Environment.